The Development of Narratological Approaches in Modern Literary Studies (Journal of Pedagogical Inventions and Practices, 2025)
This article explores the development of narratology and its transition from structuralist approaches to post-structuralist analyses. It examines the etymological and historical foundations of narratology, tracing the evolution of broad and narrow concepts of narrative from Aristotle’s Poetics. The study also highlights how narratology has been formed and developed across various literary genres and artistic texts. Furthermore, the paper discusses the limitations and potentials of applying structuralist methods in the analysis of artistic narratives, while introducing post-structuralist methodologies that offer new perspectives for literary interpretation.